Sustainable Landscape Construction: Materials and Products — Wood - Gail Hansen (EDIS)
ENH1142, a 1-page fact sheet by Gail Hansen, highlights several landscape construction strategies to reduce wood waste and environmental impact. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.